Konsep al-Talfīq dan Hukumnya dalam Satu Ibadah Menurut Perspektif Empat Mazhab - Muhammad Istiqamah; Muhammad Muhammad; Islahuddin Ramadhan Mubarak; Riki Rivaldi Sagena (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to know and understand the concepts and laws of al-Talfīq in worship according to the perspectives of the four schools of thought. The problems that researchers raise in this study are; what are the concepts and laws of al-Talfīq in worship according to the perspective of the four schools of thought? This research uses a type of qualitative descriptive research (non-statistical), which focuses on the study of manuscripts and texts, using historical normative and philosophical approaches. The research results found are as follows; Talfiq is a method of merging two or more schools of thought to issue a new opinion (qaul al-Jadi). In addition, al-Talfiq is sometimes used by someone to get out of a difficult position by taking many different opinions without any superiority (tarjīḥ) between them. Regarding the law, the scholars have different opinions, some allow it absolutely, absolutely forbid it, and some allow it and some others prohibit it depending on certain criteria or conditions. Regarding the law, the scholars have different opinions, some allow it absolutely, absolutely forbid it, and some allow it with conditions, that is, there is no reason to seek the lightest thing without excuse, it doesn't cancel the legal judge, and it doesn't disagree with the consensus opinion.